Distribution law of corrosion pits on steel suspension wires for a tied arch bridge. Issue 3 (3rd May 2016) - Miao, Changqing; Yu, Jie; Mei, Mingxing
Abstract : Purpose: This paper aims to research steel wire corrosion pitting distribution characteristics and evolution, the shape, number and size of corrosion pits from one tied arch bridge were tested, analyzed and researched. Design/methodology/approach: The probability distribution model of corrosion pits of different shapes was established, and the law of corrosion pit growth and evolution was researched. The relationship between the steel wire local corrosion parameters and the average degree of corrosion was explored. Findings: The results revealed that the pits of steel wires can be divided into four categories of shapes: a deep ellipsoidal shape, a shallow ellipsoidal shape, a groove shape and a saddle shape. When developing to a certain degree, the small dark narrow type corrosion pit will turn into a large open pit of either a shallow ellipsoidal shape, a groove shape or a saddle shape. Originality/value: The maximum depth of the corrosion pits was close to the Weibull distribution, and the maximum width and length of the wire corrosion pits were close to the logarithmic normal distribution, causing a large error when using a uniform corrosion model of steel wire mechanics.